Fe3O4 nanoparticles three-dimensional electro-peroxydisulfate for improving tetracycline degradation. (April 2021) - Tang, Shoufeng; Zhao, Mengzhen; Yuan, Deling; Li, Xue; Wang, Zetao; Zhang, Xiaoyu; Jiao, Tifeng; Ke, Jun
Abstract: In this work, Fe3 O4 nanoparticle employed as the three-dimensional electrode, were introduced into the electro-oxidation system with peroxydisulfate to improve the tetracycline (TC) degradation. The coprecipitation method prepared Fe3 O4 was proved to be the irregular sphere-like form through the characterizations of XRD, SEM, N2 adsorption isotherms, and XPS. By the contrast experiments, the EO-Fe3 O4 -PDS exhibited the outstanding TC degradation capability, which achieved 86.53% after 60 min treatment with current intensity of 20 mA cm −2, Fe3 O4 dose of 0.2 g L −1, PDS amount of 2 mmol L −1, initial pH 4.5, and TC concentration of 25 mg L −1 . Besides, the influence of current intensity, Fe3 O4 dosage, PDS concentration, and beginning pH on the TC degradation was investigated systemically. The consecutive five recycles of Fe3 O4 demonstrated that a favorable stability for the coupling process. The EO-Fe3 O4 -PDS could improve the PDS decomposition and H2 O2 production. The sulfate and hydroxyl radicals both took charge of the antibiotic degradation as certified by scavenger test. The TC degradation evolution was presented based on the HPLC-MS analyses of degradation byproducts. Highlights: The EO -Fe3 O4 -PDS was established for tetracycline degradation. Sulfate and hydroxyl radicals both worked for the tetracycline removal in the synergy. The synergistic mechanism of the EO-Fe3 O4 -PDS system was proposed.